In-situ formation of one-dimensional coordination polymers in molecular junctions - Anton Vladyka (Nature Portfolio, 2019)
Organometallic frameworks have raised considerable interest in the area of nanoelectronics, but they are usually prepared at the ensemble level resulting in limited control. Vladyka et al. control the formation of single oligomer chains, unit by unit, in a mechanically controllable break-junction setup.